PROTECTIVE ROLE OF FENUGREEK LEAF EXTRACT AND QUERCETIN AGAINST PETROL EXHAUST NANOPARTICLE INDUCED LIPID PEROXIDATION AND OXIDATIVE STRESS IN RAT ERYTHROCYTES IN VITRO - M, Durga; S, Nathiya; T, Devasena (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective & Methods: Inhaled nanoparticles of air borne origin enter the bloodstream and react with the circulatory system leading to cardiovascular and systemic events. Fenugreek (Trigonella foecum-graecum) and quercetin are known for their antioxidant and antitoxic potentials. To understand this mechanism we studied in detail the interaction of petrol exhaust nanoparticles (PEPs) treated with or without aqueous fenugreek leaf extract (EXT) or quercetin (Q) in rat erythrocytes (RBC) invitro. Results: Incubation of RBCs with PEP alone (1, 10 and 100 Âµg/ml) for 60 mins caused highest hemolytic activity (~upto 46%). Erythrocyte susceptibility to lipid peroxidation (invitro) measured by malondialdehyde content (MDA) showed significant dose dependent increase in MDA. The superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) activities were found to significantly decrease (p<0.05) in a dose dependent manner when compared to the control. The glutathione S transferase (GST) levels was found to increase significantly (p<0.05) in the PEP treated groups. Prior treatment with the EXT or Q showed replenishments of antioxidant levels and brought the values to near normal, hence proving the protective effect of EXT or Q. Conclusion: The phytochemicals in the EXT could play a key role in protecting the RBC cells against the petrol exhaust nanoparticle induced toxicity. Thus, the study demonstrates PEP induced erythrocyte toxicity in a dose dependent manner and the alleviative effects of the EXT and Q.